Intestinal parasitic infection among the HIV-infected patients in Nepal - Bishnu Raj Tiwari; Prakash Ghimire; Sarala Malla; Bimala Sharma; Surendra Karki (Journal of Infection in Developing Countries)
Introduction: Intestinal parasitic infection has been a significant problem in HIV patients, worldwide. In this study, we aimed to measure the prevalence and identify the factors associated with intestinal parasitic infection in people infected with HIV and attending National Public Health Laboratory in Kathmandu, Nepal, for CD4 T-cell count.